Exploration of the regulatory mechanisms of regeneration, anti-oxidation, anti-aging and the immune response at the post-molt stage of Eriocheir sinensis - Wang, Meiyao; Ge, Jiachun; Ma, Xingkong; Su, Shengyan; Tian, Can; Li, Jianlin; Yu, Fan; Li, Hongxia; Song, Changyou; Gao, Jiancao; Xu, Pao; Tang, Yongkai; et al. (Frontiers in Physiology, 2022)
The Yangtze River is the third-longest river in the world and is a habitat for Eriocheir sinensis (E. sinensis), an economically valuable anadromous crustacean. E. sinensis is widely appreciated by the surrounding population due to its culinary delicacy and rich nutrients. The E. sinensis breeding industry is very prosperous and molting is one of the important growth characteristics. Death during the post-molt stage is a major bottleneck for the E. sinensis breeding industry. Investigation of the regulatory mechanisms for E. sinensis after molting may provide a strong theoretical foundation to improve the quality of cultivation. In contrast to vertebrates, the heart tissue of E. sinensis has a strong capacity to regenerate. Research on the regulation of molting in E. sinensis is still in the initial stages. There is currently no relevant information on the regulatory mechanisms of heart development following molting, hence the importance of exploring these mechanisms in detail. High-throughput sequencing is an essential technique used to carry out systematic and preliminary research on the physiological regulation mechanisms of organisms. Comparative transcriptome analysis was used to study developmental regulation mechanisms in the heart of E. sinensis at the post-molt and inter-molt stages. The results indicated that many regulatory pathways and genes involved in regeneration, anti-oxidation, anti-aging and the immune response were significantly upregulated after molting in E. sinensis. Aside from cardiac development, the differentially expressed genes (DEGs) were relevant to myocardial movement and neuronal signal transduction. DEGs were also related to the regulation of glutathione homeostasis and biological rhythms in regard to anti-oxidation and anti-aging, and to the regulation of immune cell development and the immune response. This is the first study of the regulatory mechanisms involved in heart development in E. sinensis after molting. As such, it provides a theoretical framework for understanding the regulation of molting in E. sinensis and in other economically important crustaceans. Many regulatory pathways relevant to anti-oxidation and anti-aging were found to be upregulated after molting in E. sinensis, thus providing a theoretical basis for further research into organ regeneration in vertebrates.